Love and Empire : Cybermarriage and Citizenship across the Americas - Schaeffer, Felicity Amaya (Book collections on Project MUSE., 2012)
The spread of the Internet is remaking marriage markets, altering the process of courtship and the geographic trajectory of intimacy in the 21st century. For some Latin American women and U.S. men, the advent of the cybermarriage industry offers new opportunities for re-making themselves and their futures, overthrowing the common narrative of trafficking and exploitation. In this engaging, stimulating virtual ethnography, Felicity Amaya Schaeffer follows couples' romantic interludes at "Vacation Romance Tours," in chat rooms, and interviews married couples in the United States in order to un.